Clinical efficacy of anti‐glycopeptidolipid‐core IgA test for diagnosing Mycobacterium avium complex infection in lung. Issue 8 (4th September 2015) - Numata, Takanori; Araya, Jun; Yoshii, Yutaka; Shimizu, Kenichiro; Hara, Hiromichi; Nakayama, Katsutoshi; Kuwano, Kazuyoshi
Abstract Background and objective It is difficult to verify the bacteriological diagnosis of Mycobacterium avium complex (MAC) infection. The anti‐glycopeptidolipid (GPL)‐core IgA antibody test was recently developed as a diagnostic method for MAC pulmonary disease. Only a few studies evaluate its clinical efficacy. We conducted retrospective evaluations of clinical characteristics of patients suspected of MAC infection to explore the usefulness of the anti‐GPL‐core IgA antibody test. Methods We retrospectively evaluated 296 patients who were suspected to have MAC infection and underwent anti‐GPL‐core IgA antibody test between March 2013 and July 2014 in Jikei University hospital. Results A total of 29 patients were diagnosed with 'definite MAC' based on the American Thoracic Society (ATS) criteria with multiple identifications of MAC. On the other hand, 106 patients were diagnosed with other pulmonary diseases than MAC. The sensitivity and specificity of anti‐GPL‐core IgA antibody test for MAC diagnosis were 58.6% and 98.1%, respectively. The definite MAC group showed no significant differences in strains, treatment history or number of segments involved. The duration of MAC disease in the positive‐antibody group was significantly longer than in the negative‐antibody group (P = 0.046). A significant increase in the false‐negative rate was observed in patients with malignant disease (P = 0.029). Conclusions The anti‐GPL‐core IgA antibody test demonstrated high sensitivity and specificity for the diagnosis of MAC infection especially in patients without malignant diseases.